Mapping the Landscape of Accounting Education Quality Research: A Bibliometric Review (Public Accounting and Sustainability, 2024)
Research aims: This study aims to map the literature on accounting education quality worldwide through bibliometric analysis. Design/Methodology/Approach: Data were obtained from the Scopus database and then bibliometrically analyzed using Bibliometrix's R package, Biblioshiny. This analysis focused on studies on accounting education quality published in the form of English articles with the query used, namely TITLE-ABS-KEY (“accounting education" AND "quality") AND (LIMIT-TO (DOCTYPE, "ar")) AND (LIMIT-TO (LANGUAGE, "English")). The research sample contained 142 scientific articles from 78 journals from 1983 to 2024. Research findings: Based on the bibliometric analysis, the results of the study could map the literature on accounting education quality, which includes the most cited research trends, namely research on factors of students' intention to major in accounting and non-accounting science studied by Tan and Laswad (2006); Watty K became the most influential author; the most searched keyword is "accounting education"; the network of collaboration on accounting education quality remains minimal; and research topics have been mapped in four main themes (motor, niche, emerging or declining, basic). Future research themes in accounting can focus on curriculum development, the impact of technology, professional ethics, and the effectiveness of online/blended/hybrid learning, considering graduate work readiness and the quality of accounting education. Theoretical contribution/Originality: This research guides other researchers in exploring potential topics on accounting education quality. Practitioner/Policy implication: The results of this study can be used to identify the development of accounting education quality, become the basis for policies and initiatives that support the growth of international collaboration, and create opportunities for collaboration between researchers. Research limitation/Implication: The limitation of this research is that it only analyzed articles published in the Scopus database.